Does Fe accumulation in durum wheat seeds benefit from improved whole-plant sulfur nutrition?. (September 2018) - Astolfi, Stefania; Pii, Youry; Terzano, Roberto; Mimmo, Tanja; Celletti, Silvia; Allegretta, Ignazio; Lafiandra, Domenico; Cesco, Stefano
Abstract: Sulfur and iron balanced supply is of paramount importance for plants, since Fe homoeostasis in plants has been shown to be strongly dependent on sulfate availability; vice versa the adaptation to Fe deficiency requires the adjustment of S uptake and assimilation rate. Interestingly, it has been demonstrated that providing S above adequate concentrations may enhance Fe use efficiency in wheat and this effect seems to be especially advantageous for plants grown under severe Fe shortage. Therefore, the investigation of sulfate effect on Fe uptake and allocation in crop could be of great significance. Aim of this study was to clarify in wheat at both leaf and seed level whether and to what extent the changes in S and Fe supply affect concentration and distribution of sulfate and also how different availability of S changes the mineral concentration and distribution in wheat adequately or poorly fed with Fe. Obtained results showed how plants recovered from Fe deficiency stress by means of a tuned S fertilization, without additional input of Fe fertilizers. Also, with decreasing Fe availability the Zn concentration of grains significantly increased, suggesting that a balanced crop Fe nutrition could allow a successful biofortification of wheat grains with Zn. Highlights: S supply is a significant factor affecting wheat shoots and seeds nutrients content. Plants recovered from Fe deficiency stress by means of a tuned S fertilization. With decreasing Fe availability, the Zn concentration of grains significantly increased.